1993
DOI: 10.1113/jphysiol.1993.sp019567
|View full text |Cite
|
Sign up to set email alerts
|

Ca(2+)‐dependent K+ channels of high conductance in smooth muscle cells isolated from rat cerebral arteries.

Abstract: SUMMARY1. Cerebrovascular smooth muscle cells (CVSMCs) were dispersed from cerebral arteries of adult rats using collagenase and trypsin. The extracellular patch clamp technique was used to study single calcium-activated potassium channels, K+c channels, in these cells at 21-23 'C.2. Whole-cell, current clamp recordings showed that isolated CVSMCs possessed a mean resting potential of -41 + 7-4 mV (n = 69), an input resistance of 3-2 + 0-49 GQ (n = 20) and a capacitance of 24+2-3 pF (n = 7).3. Inside-out patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 35 publications
7
26
0
Order By: Relevance
“…Other reports describe BK currents ranging from hundreds of pA to a few nA [37,38,39,40,41]. It has been noted that these were at less depolarized membrane potentials (40–60 mV) where there may be less BK activation and currents observed here at those membrane potentials are similar to those reported in rat basilar artery, rabbit arcuate artery, mouse colon smooth muscle and human coronary-artery smooth muscle [35,36,37,38,39]. …”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Other reports describe BK currents ranging from hundreds of pA to a few nA [37,38,39,40,41]. It has been noted that these were at less depolarized membrane potentials (40–60 mV) where there may be less BK activation and currents observed here at those membrane potentials are similar to those reported in rat basilar artery, rabbit arcuate artery, mouse colon smooth muscle and human coronary-artery smooth muscle [35,36,37,38,39]. …”
Section: Discussionsupporting
confidence: 73%
“…3c, p > 0.58). The resulting slope factors resemble those reported for cloned dog BK channels expressed in human embryonic kidney cells (15.1 mV, α subunit alone compared to 14–15 mV in this study) [33] and oocytes (11.9–14.1 mV, α + β1 subunits) [34] and do not differ from those observed by other investigators in resistance cerebral arteries from rats (14–16 mV) [35, 36]. Additionally, investigators have found close agreement between the macroscopic methods employed here to determine BK voltage dependency and estimates from single-channel records from the same arterial tissue [11, 34].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…6), which is consistent with the report that the ACh-activated single channel has a very low open probability in physiological voltage range even with a very high agonist concentration (ACh 500 μM, Inoue et al, 1993). This is not surprising because the single VSMC has a high R input (3-10 GΩ in dispersed VSMCs, Hirst et al, 1989;Wang et al, 1993)). According to Ohm's law, a 2 pA current should roughly cause a 6-20 mV depolarization in cells of 3-10 GΩ, which is about the size of ACh-depolarization from intracellular recordings (Figs.…”
Section: Technical Issuessupporting
confidence: 79%
“…Recently, it is reported that internally applied TEA blocks the Ca-dependent K+ channels with high sen sitivity (14), suggesting a difference in the internal pore (15) of the channels in rat cerebral artery compared with other tissues. Thus, the internal binding site for TAAs in the KATP channels in vascular smooth muscles seems differ ent from that in cardiac or skeletal muscles.…”
mentioning
confidence: 99%